Aldosterone activates the oncogenic signals ERK1/2 and STAT3 via redox‐regulated mechanisms. Issue 8 (30th March 2017) - Queisser, Nina; Schupp, Nicole; Schwarz, Eva; Hartmann, Christina; Mackenzie, Gerardo G.; Oteiza, Patricia I.
Abstract : Epidemiological studies found an increased risk for kidney cancer in hypertensive patients, of which a subgroup has high aldosterone (Ald) levels. We recently showed that Ald is genotoxic both in kidney tubular cells and in rats with mineralocorticoid‐mediated hypertension. The present work investigated in vitro and in vivo, if the oxidative stress‐mediated activation of the ERK1/2 pathway, and its downstream target STAT3, could be one mechanism involved in the potential oncogenic capability of excess Ald exposure. The effects of excess Ald were investigated in LLC‐PK1 cells and in Ald‐induced hypertensive rats. Ald caused cRaf, MEK1/2, and ERK1/2 phosphorylation both in LLC‐PK1 cells and in rat kidneys. ERK1/2 activation led to an increased phosphorylation of MSK1, p90RSK, and STAT3. The involvement of ERK1/2 in the activation of STAT3 was evidenced by the capacity of the MEK inhibitor U0126 to prevent Ald‐mediated ERK1/2 and STAT3 phosphorylation. Both in vitro and in vivo, the activation of ERK1/2 and STAT3 by Ald was dependent on the mineralocorticoid receptor and was triggered by an increase in cellular oxidants. Ald‐mediated oxidant increase was in part due to the activation of the enzymes NADPH oxidase and NO synthase. Proliferation was significantly enhanced and apoptosis decreased in Ald‐treated rat kidneys and/or LLC‐PK1 cells. Results support the concept that the oxidant‐mediated long‐term activation of ERK1/2/STAT3 by persistently high Ald levels could trigger proliferative and prosurvival events. Ald‐mediated promotion of cell survival and DNA damage could result in kidney cell transformation and initiation of cancer in hypertensive patients with hyperaldosteronism.